2015
DOI: 10.1021/acs.jafc.5b04439
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Target Proteins of Mangiferin in Mice with Acute Lung Injury Using Functionalized Magnetic Microspheres Based on Click Chemistry

Abstract: Prevention of the occurrence and development of inflammation is a vital therapeutic strategy for treating acute lung injury (ALI). Increasing evidence has shown that a wealth of ingredients from natural foods and plants have potential anti-inflammatory activity. In the present study, mangiferin, a natural C-glucosyl xanthone that is primarily obtained from the peels and kernels of mango fruits and the bark of the Mangifera indica L. tree, alleviated the inflammatory responses in lipopolysaccharide (LPS)-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…In addition, mangiferin obviously prevented lung inflammation via inhibiting proinflammatory mediators and enzyme production (TNF-α, IL-6, IL-8, COX-2, iNOS, PGE2 and NO), inhibited oxidative stress via promoting antioxidant enzyme levels (SOD, GSH and CAT) and attenuated apoptosis via regulating Bax/Bcl-2, Caspase 9 and Caspase 8. Concerning the underlying mechanism, this compound obviously suppressed MAPK and NF-κB signaling and up-regulated the Nrf2-HO-1 signaling pathway [ [133] , [134] , [135] , [136] ]. Additionally, these protective effects of mangiferin were also associated with Hspa5 and Ywhae, which could subsequently down-regulate the MAPK signaling pathway.…”
Section: Natural Compounds That Exert Anti-ali Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, mangiferin obviously prevented lung inflammation via inhibiting proinflammatory mediators and enzyme production (TNF-α, IL-6, IL-8, COX-2, iNOS, PGE2 and NO), inhibited oxidative stress via promoting antioxidant enzyme levels (SOD, GSH and CAT) and attenuated apoptosis via regulating Bax/Bcl-2, Caspase 9 and Caspase 8. Concerning the underlying mechanism, this compound obviously suppressed MAPK and NF-κB signaling and up-regulated the Nrf2-HO-1 signaling pathway [ [133] , [134] , [135] , [136] ]. Additionally, these protective effects of mangiferin were also associated with Hspa5 and Ywhae, which could subsequently down-regulate the MAPK signaling pathway.…”
Section: Natural Compounds That Exert Anti-ali Effectsmentioning
confidence: 99%
“…Additionally, these protective effects of mangiferin were also associated with Hspa5 and Ywhae, which could subsequently down-regulate the MAPK signaling pathway. Interestingly, 30 mg/kg mangiferin gave slightly stronger lung protection than 1 mg/kg DEX in LPS-induced ALI mice [ 133 ].…”
Section: Natural Compounds That Exert Anti-ali Effectsmentioning
confidence: 99%
“…Another study showed that mangiferin exhibits its anti‐inflammatory activity by activating superoxide dismutase and reducing the levels of malonaldehyde and COX‐2 mRNA along with some other cytokines in animals with lung injury . Moreover, in acute lung injury, mangiferin is capable in alleviating the inflammatory responses by down regulating the MAP kinase signaling pathways . In addition, mangiferin also exhibits antispasmodic effects by activating the nitric oxide‐cyclic GMP pathway and thereby preventing tracheal contractions is guinea pig .…”
Section: Effect Of Mangiferin Against Inflammation Related Organ Dysfmentioning
confidence: 99%
“…Using a DNA hybridization array, Leiro et al found that MGF had significant impacts on the profiles of a large number of NF‐κB related cytokine genes that are critical for regulation of inflammation . More recent studies reported MGF's ability to suppress IKK‐β/NF‐κB and/or MAPK/ERK/JNK signaling pathways in lymphoid organs , leucocytes , diabetic kidneys , and heart , acutely injured liver , colon and lungs , and to inhibit NF‐kB DNA binding and IKK activity in HepG2 cells .…”
Section: Mgf Modulates Cross Talk Between Lipid Metabolism and Carbohmentioning
confidence: 99%